The Role of Organizations in Taking Care Life Harmonization Between Religious Communities - Huda, Ulul; Haryanto, Tenang (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
Research has been conducted on community interactions that can produce tolerance to create harmony in diversity in Banyumas Regency. The specific objectives of this study are: first to find patterns of interaction that occur in the heterogeneous Banyumas community. The second objective is to explore the concept of community views on diversity. Third, it reveals the involvement of organizations and or communities that intersect with issues of tolerance in creating a conducive religious atmosphere in Banyumas Regency. This research was conducted by gathering information and analyzing the harmony of the community in Banyumas Regency. This research is qualitative and analytic descriptive. This method is carried out to solve actual problems by collecting data, compiling or classifying, analyzing and interpreting it using multicultural education theory and then drawing conclusions. This research focuses on the embodiment of the harmony pattern of Banyumas community diversity through FKUB, SMLI and FORSA. These three organizations have a real contribution in the formation of a harmony society in diversity in Banyumas Regency. The results of this study show that the harmony of religions in Banyumas regency has been successfully carried out because there is no mutual suspicion of interfaith leaders and have the same understanding of